Strategy for identification of Hoax News in digital media in facing case of racism of Papua students in Indonesia - Siahaan, Chontina; Nahria, Nahria; Tampubolon, Manotar (Technium Social Sciences Journal, 2021)
The amount of hoax information spread about the case of racism of Papuan students in Surabaya can certainly trigger conflict. Therefore, Papuan students are required to be able to properly analyze information obtained from any source, especially from digital media. This study aims to determine the strategy of Papuan students in identifying hoax news about cases of racism in digital media. This study uses qualitative methods with data collection techniques consisting of observation, in-depth interviews, documentation and focus group discussions. The informants consisted of Papuan students in Jayapura and Jakarta. Data analysis uses data reduction, data display and conclusion/verification. The results showed that student literacy about hoaxes consisted of (1) hoaxes were confusing and provocative information, (2) hoaxes were news diversion issues, (3) untrue news and (4) hoaxes sourced from the community and the state. Related to how Papuan students identify hoaxes, they are (a) looking for comparative information on other media, (b) checking and rechecking with friends and family, and (c) checking the clarity of information sources. To be critical of hoax news, students are criticizing hoaxes against images, photos and news that are not appropriate, criticizing foreign media and domestic media that spread hoaxes, and criticizing the government as a hoax spreader. The recommendation for this research is that the government makes an electronic-based information system that can be used by the Papuan people as a means to find out the government’s efforts in educating and educating the Papuan people in the field of Digital Media Literacy.